In Vivo Consequences of Disrupting SH3-Mediated Interactions of the Inducible T-Cell Kinase. (9th May 2012) - Levytskyy, Roman M.; Hirve, Nupura; Guimond, David M.; Min, Lie; Andreotti, Amy H.; Tsoukas, Constantine D.
Abstract : ITK-SH3-mediated interactions, both with exogenous ligands and via intermolecular self-association with ITK-SH2, have been shown to be important for regulation of ITK activity. The biological significance of these competing SH3 interactions is not completely understood. A mutant of ITK where substitution of the SH3 domain with that of the related kinase BTK (ITK-BTK(SH3) ) was used to disrupt intermolecular self-association of ITK while maintaining canonical binding to exogenous ligands such as SLP-76. ITK-BTK(SH3) displays reduced association with SLP-76 leading to inefficient transphosphorylation, reduced phosphorylation of PLCγ1, and diminished Th2 cytokine production. In contrast, ITK-BTK(SH3) displays no defect in its localization to the T-cell-APC contact site. Another mutation, Y511F, in the activation loop of ITK, impairs ITK activation. T cells expressing ITK-Y511F display defective phosphorylation of ITK and its downstream target PLCγ1, as well as significant inhibition of Th2 cytokines. In contrast, the inducible localization of ITK-Y511F to the T cell-APC contact site and its association with SLP-76 are not affected. The presented data lend further support to the hypothesis that precise interactions between ITK and its signaling partners are required to support ITK signaling downstream of the TCR.